2023
DOI: 10.1001/jamanetworkopen.2023.36030
|View full text |Cite
|
Sign up to set email alerts
|

Primary Care Practitioner Perspectives on the Role of Primary Care in Dementia Diagnosis and Care

Alissa Bernstein Sideman,
Melissa Ma,
Alma Hernandez de Jesus
et al.

Abstract: ImportanceAlthough the barriers to dementia care in primary care are well characterized, primary care practitioner (PCP) perspectives could be used to support the design of values-aligned dementia care pathways that strengthen the role of primary care.ObjectiveTo describe PCP perspectives on their role in dementia diagnosis and care.Design, Setting, and ParticipationIn this qualitative study, interviews were conducted with 39 PCPs (medical doctors, nurse practitioners, and doctors of osteopathic medicine) in C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…The FLC involvement in the clinic benefited team members by allowing them to focus on their roles knowing that caregivers were being supported, and by learning about available community and Alzheimer Society services. Rural family physicians recognize caregivers’ need for education and emotional support and see this as part of their role [ 21 , 53 ] but like many primary care physicians they lack the resources and time needed to provide ongoing care management and support [ 22 , 24 ]. Heintz et al [ 22 ] assert that within collaborative care teams, dementia care managers, which share many facets of the FLC role, can ensure that PLWD and caregivers have access to the information and support needed to obtain services, while also improving primary care providers’ work lives and sense of competence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The FLC involvement in the clinic benefited team members by allowing them to focus on their roles knowing that caregivers were being supported, and by learning about available community and Alzheimer Society services. Rural family physicians recognize caregivers’ need for education and emotional support and see this as part of their role [ 21 , 53 ] but like many primary care physicians they lack the resources and time needed to provide ongoing care management and support [ 22 , 24 ]. Heintz et al [ 22 ] assert that within collaborative care teams, dementia care managers, which share many facets of the FLC role, can ensure that PLWD and caregivers have access to the information and support needed to obtain services, while also improving primary care providers’ work lives and sense of competence.…”
Section: Discussionmentioning
confidence: 99%
“…Bayly et al [ 3 ] conducted a review of dementia service availability in rural areas that identified strategies to address service use barriers, including a point of contact to assist in accessing services that matched individual needs. Primary care physicians often lack adequate time and reimbursement systems needed to manage all the complexities of dementia care such as education and care coordination [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the Original Investigation titled “Primary Care Practitioner Perspectives on the Role of Primary Care in Dementia Diagnosis and Care,” 1 published September 28, 2023, “practitioner” was misspelled in the title. This article has been corrected.…”
mentioning
confidence: 99%